2019
DOI: 10.7717/peerj.6641
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability in zooplankton community in the western Yellow Sea and its possible links to green tides

Abstract: Large-scale macro-algal blooms ofUlva prolifera(also called green tides) have appeared each summer since 2008 in the western Yellow Sea. In this study, we investigated the temporal variability in zooplankton community in the western Yellow Sea and its possible links to green tides using data from a long-term plankton survey off the coast of Qingdao, China. Environmental conditions observed in the study area during the green tide period (GTP: June–August, 2008–2013) were compared to the non-green tide period (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…Chl hotspots are distributed in a long curving band near 123°E and a northward boundary around 32°N. Wang et al (2019) reported that the Chl concentration surged in late April and peaked in mid-June, consistent with our findings. Although the Chl concentration in the spawning sites in southern Jiangsu is lower than that at hotspots (29-30°N), salinity is a limiting factor in the reproductive activities of the small yellow croaker.…”
Section: Figuresupporting
confidence: 92%
See 1 more Smart Citation
“…Chl hotspots are distributed in a long curving band near 123°E and a northward boundary around 32°N. Wang et al (2019) reported that the Chl concentration surged in late April and peaked in mid-June, consistent with our findings. Although the Chl concentration in the spawning sites in southern Jiangsu is lower than that at hotspots (29-30°N), salinity is a limiting factor in the reproductive activities of the small yellow croaker.…”
Section: Figuresupporting
confidence: 92%
“…The influential process of the green tide outbreak on fishery resources was extremely complex. The green tide was reported to mainly affect the primary production process in the ocean and endanger the survival rate of the fish larvae through the food chain (Wang et al, 2019;Sun et al, 2022). Sun et al (2022) regarded the outbreak of U. prolifera as an event to simulate the natural death of the small yellow croaker and indicated at least 10% of biomass and catch loss of the small yellow croaker in the case of the surging natural death.…”
Section: Figurementioning
confidence: 99%
“…U. prolifera generally floats on the surface of seawater, posing a serious threat to coastal tourism, fishery and environment [3,4]. The outbreak of U. prolifera green tide affects not only the nutrient contents of seawater but also the interactions among marine organisms, and further influences the marine biogeochemical cycles [5][6][7][8]. During the decomposing process of U. prolifera, it can consume dissolved oxygen resulting in water hypoxia or even anoxia, and also release hydrogen sulfide into seawater, which is hazardous to marine organisms [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a million tons of green tide biomass accumulated in the coastal waters of the Shandong Peninsula in late June and July (Liu et al, 2016). The resources available to artificially collect algae are limited, and as the green tide enters the dissipation phase, some of the algae from the green tide will be washed ashore by waves and tides, and affect the ecological environment and human activities in the coastal areas, Some of it will decompose naturally in the sea, releasing a large amount of nutrients and changing the ecology of the marine environment (Chimney and Pietro, 2006;Wang et al, 2012), affecting other biological groups in the water body (Wang et al, 2019), affecting other biological groups in the water body and increasing the likelihood of secondary marine disasters such as red tides (Kong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%